1997
DOI: 10.1021/bi962522q
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Structure of Tetrahydrodipicolinate N-Succinyltransferase,

Abstract: The conversion of tetrahydrodipicolinate and succinyl-CoA to N-succinyltetrahydrodipicolinate and CoA is catalyzed by tetrahydrodipicolinate N-succinyltransferase and is the committed step in the succinylase pathway by which bacteria synthesize L-lysine and meso-diaminopimelate, a component of peptidoglycan. The X-ray crystal structure of THDP succinyltransferase has been determined to 2.2 A resolution and has been refined to a crystallographic R-factor of 17.0%. The enzyme is trimeric and displays the left-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 24 publications
(37 reference statements)
5
85
0
Order By: Relevance
“…Although the asymmetric unit in both structures contains a single protomer of PglD, the homotrimer is observed centered on a crystallographic 3-fold axis. As seen in the structures of several other proteins that contain a hexapeptide repeat motif (37)(38)(39)(40)(41), aliphatic residues in the L␤H domain form the core of interactions between protomers in the PglD homotrimer. In the citrate-bound structure, one citrate molecule occupies each of the coenzyme binding sites (discussed below), and the carboxylate group at position C3 of citrate hydrogen bonds with the side chains of His-134-a, Asn-118-a, and Glu-124-b (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the asymmetric unit in both structures contains a single protomer of PglD, the homotrimer is observed centered on a crystallographic 3-fold axis. As seen in the structures of several other proteins that contain a hexapeptide repeat motif (37)(38)(39)(40)(41), aliphatic residues in the L␤H domain form the core of interactions between protomers in the PglD homotrimer. In the citrate-bound structure, one citrate molecule occupies each of the coenzyme binding sites (discussed below), and the carboxylate group at position C3 of citrate hydrogen bonds with the side chains of His-134-a, Asn-118-a, and Glu-124-b (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of E. coli LpxA at 2.6-Å resolution suggests that the enzyme is homotrimer in which the active sites are situated between adjacent subunits (9 -11). Each LpxA monomer is constructed around an unusual left-handed parallel ␤-helix, which is conserved in all LpxA orthologs and in many other bacterial acetyl-and acyltransferases (9,(31)(32)(33). The crystal structure of E. coli LpxA has not been determined in the presence of bound substrates or substrate analogs, but sitedirected mutagenesis has demonstrated that histidine 125 is crucial for activity and that adjacent basic residues may contribute to substrate binding (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…coli LpxA (a homotrimer) contains multiple contiguous hexad repeats (51), which are also found in certain other acyltransferases and acetyltransferases (52)(53)(54). The X-ray structure of LpxA shows that these hexads specify a novel protein fold, consisting of a left-handed helix of short parallel ␤-sheets (51).…”
Section: The Constitutive Lipid a (Endotoxin) Pathwaymentioning
confidence: 99%